SMALL BUSINESS DEVELOPMENT IN UZBEKISTAN - Kamolov, Dostonbek; Qilicheva, Rukhshona (Science technology&Digital finance, 2023)
The article will talk about small business and private entrepreneurship, which are the main sectors that develop the economy, and about the development of small business and private entrepreneurship.